2013
DOI: 10.1007/s12031-013-0012-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy via p53-Mediated Disruption of ULK1 in a SCA7 Polyglutamine Disease Model

Abstract: However, recently evidence implicating autophagic dysfunction in these disorders has also been reported. In this study we show that the SCA7 polyglutamine protein ataxin-7 (ATXN7) reduces the autophagic activity via a previously unreported mechanism involving p53-mediated disruption of two key proteins involved in autophagy initiation. We show that in mutant ATXN7 cells, an increased p53-FIP200 interaction and co-aggregation of p53-FIP200 into ATXN7 aggregates result in decreased soluble FIP200 levels and subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 51 publications
3
29
0
Order By: Relevance
“…Using the same stable inducible SCA7 model as in this study, we have previously shown that p53 co-aggregates with mutant ATXN7 and that this reduces the soluble p53 level and transcriptional activity [27]. Consistent with this, we could again in induced FLQ65 cells detect p53 in the insoluble cell fractions containing mutant ATXN7 aggregates; see Fig.…”
Section: Altered P53 Function Contributes To the Metabolic Dysfunctionsupporting
confidence: 87%
See 2 more Smart Citations
“…Using the same stable inducible SCA7 model as in this study, we have previously shown that p53 co-aggregates with mutant ATXN7 and that this reduces the soluble p53 level and transcriptional activity [27]. Consistent with this, we could again in induced FLQ65 cells detect p53 in the insoluble cell fractions containing mutant ATXN7 aggregates; see Fig.…”
Section: Altered P53 Function Contributes To the Metabolic Dysfunctionsupporting
confidence: 87%
“…9), where p53-ATXN7 coaggregation and NOX1-mediated p53 inactivation result in reduced p53 transcriptional activity, metabolic dysregulation and further NOX1 activity, as well as oxidative stress. In fact, we have shown that breaking this proposed cycle, through blockage of p53-ATXN7 co-aggregation [27], increasing p53 levels (Figs. 7-8), as well as inhibiting NOX1 activity or ROS scavenging (Fig.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…These pathways are responsible for the clearance and degradation of misfolded and/or superfluous proteins. It stands to reason that these systems are somewhat compromised in SCA patients, and numerous studies have now shown that these systems do in fact exhibit impairment in SCA diseases [61][62][63][64][65]. The dysregulation is believed to play a role in protein aggregation, as the misfolded polyQ proteins are unable to be effectively degraded, which leads to an increased proportion of aggregates.…”
Section: Protein Aggregation: a Hallmark Featurementioning
confidence: 99%
“…The group found that the inhibition of autophagy was through the co-aggregation of p53-FIP200 proteins and ataxin-7 aggregates that resulted in destabilisation of ULK1, due to decreased soluble FIP200. It was further shown that inhibition of P53 is able to restore soluble FIP200 and ULK1, which increases autophagic activity and subsequently reduces mutant ataxin-7 toxicity [62]. Therapeutic strategies targeting the pathogenic autophagic dysregulation would benefit from the understanding of the exact mechanisms by which pathogenesis is caused.…”
Section: Wild-type and Mutant Proteinmentioning
confidence: 99%